Claroideglomus etunicatum enhances Pteris vittata L. arsenic resistance and accumulation by mediating the rapid reduction and transport of arsenic in roots - Pan, Guofei; Xu, YueZhen; Li, WeiZhen; Zan, Linyan; Wang, Xueli (Frontiers in Plant Science, 2024)
Arbuscular mycorrhizal fungi (AMF) have been widely shown to promote Pteris vittata L. growth and repair under arsenic stress, but little is known about the molecular mechanism by which AMF mediate the efficient uptake of arsenic in this species. To understand how AMF mediate P. vittata arsenic metabolism under arsenic stress, we performed P. vittata root transcriptome analysis before and after Claroideglomus etunicatum (C. etunicatum) colonization. The results showed that after C. etunicatum colonization, P. vittata showed greater arsenic resistance and enrichment, and its dry weight and arsenic accumulation increased by 2.01-3.36 times. This response is due to C. etunicatum-mediated rapid reduction and upward translocation of arsenic. C. etunicatum promotes arsenic uptake by mediating MIP, PHT and NRT transporter families while increasing arsenic reduction (PvACR2 direct reduction and vesicular PvGSTF1 reduction), downregulating the expression of ABC and P-type ATPase protein families, inhibiting the compartmentalization of arsenic in roots, and promoting its translocation to leaves. This study revealed the mechanism of C. etunicatum-mediated arsenic hyperaccumulation in P. vittata, providing guidance for understanding the regulatory mechanism of P. vittata.